2019
DOI: 10.1016/j.physe.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a topological defect and Rashba spin-orbit interaction on the thermo-magnetic and optical properties of a 2D semiconductor quantum dot with Gaussian confinement

Abstract: In this paper, we examine the effect of introducing a conical disclination on the thermal and optical properties of a two dimensional GaAs quantum dot in the presence of a uniform and constant magnetic field. In particular, our model consists of a single-electron subject to a confining Gaussian potential with a spin-orbit interaction in the Rashba approach. We compute the specific heat and the magnetic susceptibility from the exact solution of the Schrödinger equation via the canonical partition function, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 71 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…For the pure hydrogen case, we use the values of the permittivity and the electron's mass in vacuum. For the GaAs impurity, we use r = 13.18 for the relative permittivity, and m * = 0.067m 0 for the effective mass [67]. Also, we choose two materials to represent the WSM: TaAs ( r = 6 [68]) and Bi 2 Se 3 ( r = 100 [69]).…”
Section: Variational Calculusmentioning
confidence: 99%
“…For the pure hydrogen case, we use the values of the permittivity and the electron's mass in vacuum. For the GaAs impurity, we use r = 13.18 for the relative permittivity, and m * = 0.067m 0 for the effective mass [67]. Also, we choose two materials to represent the WSM: TaAs ( r = 6 [68]) and Bi 2 Se 3 ( r = 100 [69]).…”
Section: Variational Calculusmentioning
confidence: 99%
“…In fact, some theoretical studies of the impact of the Rashba-SOI on the optical properties of a disk-like QD in the presence of an external magnetic field have been carried out within the framework of the density matrix approach [34]. Notably, a spin dependence of the spatial wave functions is typical in systems involving a Rashba QD in the presence of an external magnetic field, which can affect the thermo-magnetic and optical properties of a QD [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…By choosing a suitable function of the confining potential and interactions, it is possible in some cases to analytically find the energy spectrum of the system, which allows the theoretical exploration of the thermal, magnetic and optical properties of QD's. It is well established that a harmonic potential is a good approximation which reproduces the main characteristics of such systems [37,38], but it has been demonstrated that the confinement is rather anharmonic and has a finite depth which has been simulated by several authors using a Gaussian potential model [36,[39][40][41][42][43][44][45]. These works are developed in the context of the Boltzmann-Gibbs statistics, i.e., the QD under study represents the whole system which is in thermal equilibrium with an external bath.…”
Section: Introductionmentioning
confidence: 99%
“…The results of different topological defects and noninertial effects, as well as screw dislocation defect in materials, were probed. The investigation of noninertial effects and dislocation defects because of rotation for noninteracting electron gas confined in two‐dimensional pseudoharmonic QD, a conical disclination defect on thermal and optical properties of GaAs QD with Gaussian confinement, and thermal features of a particle in two‐dimensional parabolic QW including conical disclination are some significant works on disclination defects in low‐dimensional systems. In these works, different computation methods have been used to perform theoretical investigations due to various defects and external field effects.…”
Section: Introductionmentioning
confidence: 99%